Risk of osteoarthritis in patients with hidradenitis suppurativa: a global federated health network analysis - Chang, Hui-Chin; Wu, Chih-Lung; Chiu, Tsu-Man; Liao, Wen-Chieh; Gau, Shuo-Yan (Frontiers in Immunology, 2023)
Background Osteoarthritis and hidradenitis suppurativa (HS) share a common inflammatory pathway. However, whether patients with HS have higher risk developing osteoarthritis remained unclear. Methods A retrospective cohort design was adopted in this study. Electronic medical records had been retrieved from the US collaborative network in the TriNetX research network. A propensity score matching of 1:1 was performed to match for covariates. In total, 50,931 patients with HS and the same amount of non-HS controls were identified for analyses. Hazard ratio (HR) of osteoarthritis in patient with HS was calculated. Results Risk of patients with HS developing osteoarthritis was 1.37-fold higher than that of non-HS controls [95% confidence interval (CI), 1.21–1.55] when followed up for 1 year. The significance remained when the follow-up periods were extended to 3 years and 5 years. When osteoarthritis was stratified on occurring sites, the HR of knee osteoarthritis was 1.19 (95% CI, 1.09–1.29) and the HR of hip osteoarthritis was 1.17 (95% CI, 1.01–1.35) in the 5-year follow-up. The 5-year risk of osteoarthritis remained significant in sensitivity models. Conclusion Patients with HS were of high risk of developing osteoarthritis compared with people without HS. The clinical association was recommended to be considered while approaching patients with HS.